Quality of Life in Subjects Suffering from Severe Skeletal Malocclusion before Orthodontic Treatment - Tahira Kulsoom; Syed Shah Faisal; Syed Sheeraz Hussain (KARACHI MEDICAL AND DENTAL COLLEGE, 2017)
Objective: The objective of this study was to determine the occurrence of oral health impacts among patients with severe skeletal malocclusions and dentofacial skeletal deformities before orthodontic treatment. Methods: A cross-sectional study comprising of 45 adult patients referred for orthodontic or surgical- orthodontic treatment to the orthodontics department, Karachi Medical and Dental College,  Abbasi  Shaheed Hospital Karachi were  included.  The  study  group  consisted  of  29  females  and  15  males  with a mean age of 21.5 ± 5.4 years. Study was conducted for six months from 30th  Oct 2016 to 30th April 2017. A purposive sampling was done on the bases of  survey  base  study  design.  A  self-com- pleted Oral Health Impact Profile (OHIP)-14 questionnaire was used to measure the quality of life before orthodontic treatment. Inclusion criteria were subjects seeking  orthodontic  treatment  at  the  department  of  orthodontics,  den- tal OPD Karachi Medical and Dental  College,  Abbasi  Shaheed  Hospital,  Karachi,  Pakistan.  Patients  who had perceived a need for orthodontic treatment and  who  were  about  to  undergo  orthodontic  therapy were included. Subjects with chronic medical conditions, previous orthodontic  treatment,  and  craniofacial  anomalies  such as cleft lip and  palate,  untreated  dental  caries,  and  poor  periodontal  health  status  as  indicated by a community periodontal index score of 3 or more were excluded. The frequency, extent, and sever-      ity scores were calculated from the  OHIP-14.  Malocclusions  were  registered  at  clinical  examination.  The frequency and mean extent and severity scores were compared among malocclusion groups and between genders. Descriptive and inferential statistical method was applied. Results: Frequency of oral impact in malocclusion patient was  27.3%  though  test  value  was  56  (p  value >0.00). Mean value for male and female patients with malocclusion is 22.06 + 7.1 and 21.34 + 4.4 (p value >0.626), respectively, which shows no significant difference present. Mean value for class I, II and III was 24.5, 28.9 and 30.5 (p  value  >0.44),  respectively,  which  shows  no  significant differ- ence. Conclusion: There was no difference noted in the class of skeleton malocclusion in quality of life of  patients and there was no gender difference noted in oral health impact of patients.